Evaluation of the Direct and Indirect Regulation Pathways of Glutathione Target to the Hepatotoxicity of Microcystin-LR. (27th June 2018) - Zong, Wan-song; Zhang, Shu-han; Wang, Qian; Teng, Yue; Liu, Yu-zhen; Du, Yong-gang
Abstract : Glutathione (GSH) plays crucial roles in regulating the hepatotoxicity of Microcystin-LR (MCLR) by inhibiting oxidative stress or by toxin conjugation. Based on MCLR conjugation product preparation and purification, the direct and indirect regulation pathways for GSH were fully evaluated. Protein phosphatase inhibition analysis verified that GSH conjugation was an effective pathway to regulate the inhibition effect of MCLR, while GSH had slight influence on the toxicity of MCLR. Research on oxidative stress showed that both regulation pathways could reduce the formation of reactive oxygen species (stimulated by MCLR and regulated by NADH oxidase) and regulate the adverse effects on antioxidant enzymes. By evaluating the contributions for both pathways, it could be found that the indirect pathway had significant contribution to eliminating cellular reactive oxygen species and regulating protein phosphatases inhibition, while the direct regulation pathway had moderate influence. As glutathione transferases facilitated the transformation of MCLR, the hepatotoxicity of MCLR could be effectively regulated by GSH conjugation pathway, especially with abundant exogenous GSH.